2016
DOI: 10.4028/www.scientific.net/amm.835.191
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties and Microstructure of Friction Stir Welded Joints 2195-T8 Aluminum Alloy

Abstract: Friction stir welding is a widely used welding process for aluminum alloys because it avoids many of the problems of conventional fusion welding. This process is beneficial especially for lithium containing aluminum alloys in which the reactive property of element Li causes porosity and hot cracking during melting and solidification. In friction stir welding process, each region undergoes different thermo-mechanical cycles and produces a non-homogeneous microstructure. In the present study, the mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Tensile strength of 607.9 MPa was obtained for the base material. This result is comparative to the results from specimen without removing the surface oxide, which is reported earlier [4]. It is shown that by removing surface oxide before FSW, wider range of welding parameters can be obtained than that of the specimen welded without surface treatment.…”
Section: Resultssupporting
confidence: 50%
“…Tensile strength of 607.9 MPa was obtained for the base material. This result is comparative to the results from specimen without removing the surface oxide, which is reported earlier [4]. It is shown that by removing surface oxide before FSW, wider range of welding parameters can be obtained than that of the specimen welded without surface treatment.…”
Section: Resultssupporting
confidence: 50%
“…Li et al [13] studied the precipitate phase in 2195 Al–Li alloy and discovered that the precipitates in the NZ are completely dissolved in FSW. Kookil et al [14] investigated the mechanical properties of AA2195-T8 joint and achieved the maximum welding efficiency of 81%. Zhang et al [15] have studied the influence of rotation speed on the mechanical properties of AA2195-T8 joints.…”
Section: Introductionmentioning
confidence: 99%